Dapatkah Metode RGEC (Risk Profile, Good Corporate Governance, Earning, And Capital) Efektif dalam Menilai Kinerja Manajerial? Can the RGEC (Risk Profile, Good Corporate Governance, Earning, And Capital) Method be Effective in Assessing Managerial Performance? - Anggraini, Rusmalina; Setiyono, Wisnu Panggah; Rizal, As'at (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2017)
The Purpose of this Research, we tried to find the relationship between the level of bank health by using Risk Profile, Good Corporsate Governance. Earning, and Capital (RGEC) method compared with managerial performance of the Bank. Research Method, by using a descriptive quantitative approach, we attempt to describe the financial performance of the bank with new methods in accordance with guidelines and regulations issued by the financial services authority (OJK). In this research we taking financial statements data from PT. Bank Mandiri (Persero) Tbk in 2103 until 2015. Findings, we found that PT. Bank Mandiri (Persero) Tbk is in a good conditionbased on RGEC factors including: 1) Risk Profile factors measured by NPL and LDR ratios showed that the company has low risk level. 2) The implementation of Good Corporate Governance, the company had also implemented GCG principles in accordance with the provisions of OJK. 3) On earning factors assessed by ROA and NIM ratio, the company best ranked with excellent predicate value. 4) Finally on the Capital factor by employing CAR ratio, the company's position shows in a very good position. Furthermore, when this study correlated with the managerial performance, PT. Bank Mandiri was able to demonstrate an excellent managerial performance. It is shown by the increase of company's Capital Expenditure from year to year in the length of the research. Therefore, it can be concluded that if a healthy company will have an impact on improving managerial performance.